Real time mass flow rate measurement using multiple fan beam optical tomography - Ruzairi, Abdul Rahim; Lai, Chen Leong; Kok, San Chan; Mohd Hafiz Fazalul, Rahiman; Jon, Fea Pang (Elsevier, 2009)
Link to publisher's homepage at http://www.elsevier.com